2016
DOI: 10.1186/s12915-016-0295-9
|View full text |Cite
|
Sign up to set email alerts
|

The pesticidal Cry6Aa toxin from Bacillus thuringiensis is structurally similar to HlyE-family alpha pore-forming toxins

Abstract: BackgroundThe Cry6 family of proteins from Bacillus thuringiensis represents a group of powerful toxins with great potential for use in the control of coleopteran insects and of nematode parasites of importance to agriculture. These proteins are unrelated to other insecticidal toxins at the level of their primary sequences and the structure and function of these proteins has been poorly studied to date. This has inhibited our understanding of these toxins and their mode of action, along with our ability to man… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
33
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 41 publications
(35 citation statements)
references
References 49 publications
1
33
1
Order By: Relevance
“…It is well‐documented that in insects and nematodes the midgut cell lysis can be caused by Bt Cry toxins alone through pore formation (Bravo et al ., ; Deist et al ., ; Dementiev et al ., ; Peng et al ., ). However, Cry toxins alone did not effectively disrupt the midgut epithelial junctions in C. elegans (Fig.…”
Section: Discussionmentioning
confidence: 97%
“…It is well‐documented that in insects and nematodes the midgut cell lysis can be caused by Bt Cry toxins alone through pore formation (Bravo et al ., ; Deist et al ., ; Dementiev et al ., ; Peng et al ., ). However, Cry toxins alone did not effectively disrupt the midgut epithelial junctions in C. elegans (Fig.…”
Section: Discussionmentioning
confidence: 97%
“…The closest structural homologs belong to the ClyA 44–46 superfamily of bacterial pore‐forming toxins (Figure ). The best matches were two enterotoxins secreted by Bacillus cereus —HBL‐B (subunit B of hemolysin BL) and NheA (subunit A of Nhe toxin), aligned with a Z ‐score of 10.1 and 8.9, respectively, and the insecticidal Cry6Aa toxin from Bacillus thuringiensis , aligned with a Z ‐score of 9.4. The toxins consist of two sub‐domains: the tail domain made of a bundle of helices and the head domain.…”
Section: Resultsmentioning
confidence: 99%
“…To assess the relationship at the structural level, the structures of the encoded proteins were predicted by homology modelling in Phyre2 . Some of them were modeled according to the structure of Cry6Aa (as the most preferred template), even though the sequence identity with Cry6Aa was only ∼17%‐19%. The results showed that several genes coding for toxin‐like proteins are co‐localized with the ab21 gene in the genome (Figure ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations